2017
DOI: 10.1186/s12891-017-1469-5
|View full text |Cite
|
Sign up to set email alerts
|

Urdu version of the neck disability index: a reliability and validity study

Abstract: BackgroundDespite the wide use of the neck disability index (NDI) for assessing disability in patients with neck pain, the NDI has not yet been translated and validated in Urdu. The first purpose of the present study was to translate and cross-culturally adapt the NDI into the Urdu language (NDI-U). The second purpose was to investigate the reliability, validity and responsiveness of the NDI-U in Urdu-speaking patients experiencing chronic mechanical neck pain (CMNP).MethodsTranslation and cross-cultural adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
(205 reference statements)
1
15
0
2
Order By: Relevance
“…We found 14 studies that examined concurrent validity measures between GROC and another PRO 22 23 25 27–30 32 34–38. Correlations of Pearson’s and Spearman’s coefficients between GROC and another PRO were ranging from very weak to very strong correlations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 14 studies that examined concurrent validity measures between GROC and another PRO 22 23 25 27–30 32 34–38. Correlations of Pearson’s and Spearman’s coefficients between GROC and another PRO were ranging from very weak to very strong correlations.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies23 25 34 37 38 of very good-to-excellent quality reported the Pearson correlation coefficients between neck disability change scores and the GROC scores were pooled together. We found that GROC was positively correlated with disability change scores (r=0.53, 95% CI: 0.47 to 0.59, I 2 =0%).…”
Section: Resultsmentioning
confidence: 99%
“…Tem os pontos finais de "nenhuma dor" (extremidade esquerda da linha) e, "pior dor possível" (extremidade direita da linha). (9) Questionário Midas: Neste questionário, as pacientes queixosas respondem a cinco questões, atribuindo um ponto por cada dia em que, nos últimos três meses, suas atividades diárias foram limitadas pela dor. O resultado do questionário exprime-se numa pontuação que se relaciona da seguinte forma com as necessidades de tratamento: Escore 0-5 pontos (Incapacidade mínima); Escore 6-10 pontos (Incapacidade ligeira ou pouco frequente); Escore 11-20 pontos (Incapacidade moderada); Escore ≥ 21 pontos (Incapacidade grave).…”
Section: Resultsunclassified
“…or is between 0.70–0.95 [ 33 ]. The item-total correlation was calculated through Spearman’s correlation coefficient which shows the relationship strength between each item and total score of ODI-U minus the score of the item being investigated [ 34 ]. The strong relationship between two variables is considered when r value is greater than 0.7 [ 35 ].…”
Section: Methodsmentioning
confidence: 99%